Optical asymmetric key cryptography in RoFSO for high security using ring resonator system - Mitatha, Somsak; Chaiyasoonthorn, Sawatsakorn; Juleang, Pakorn (My University, 2019)
A new method for highly secured wireless transmission was proposed as optical asymmetric key cryptography in RoFSO. The optical equipment used for handling high security communication was a PANDA ring resonator and an add/drop filter. A PANDA ring resonator used the dynamic behavior of bright-bright soliton collision. The outputs of the dynamic states were used to form key suppression and key generation as a communication security application. An add/drop filter was used to recover the optical key from suppression and generate an optical asymmetric key (key for sending and key for receiving). Simulation results showed that the proposed design achieved optical asymmetric key cryptography in RoFSO. The sender's data was not perceived by an interferer because the ciphertext data signal was covered by a noiselike signal in a frequency domain of tunnel's form like a noiselike signal.
Keywords: optical cryptography; ring resonator; RoFSO; secured communication